2012
DOI: 10.1097/jto.0b013e318267cf84
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Resource Use, and Quality of Life in Paramount: A Phase III Study of Maintenance Pemetrexed Versus Placebo after Induction Pemetrexed Plus Cisplatin for Advanced Nonsquamous Non–Small-Cell Lung Cancer

Abstract: Long-term use of continuation maintenance pemetrexed was well tolerated; resource use was low, corresponding with known pemetrexed toxicities. The EQ-5D results demonstrate that patients tolerate long-term maintenance pemetrexed without worsening QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…For EQ-5D, the mean index score change from baseline ranged from 0.009 to 0.030, which is consistent with PARAMOUNT results (−0.02 to 0.01) [21]. For LCSS, the mean maximum improvements across items (0.4-24.5 mm VAS) were consistent with the JMEN study (1-11 mm VAS) [6].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…For EQ-5D, the mean index score change from baseline ranged from 0.009 to 0.030, which is consistent with PARAMOUNT results (−0.02 to 0.01) [21]. For LCSS, the mean maximum improvements across items (0.4-24.5 mm VAS) were consistent with the JMEN study (1-11 mm VAS) [6].…”
Section: Discussionsupporting
confidence: 70%
“…A larger proportion of patients (38%, 20 patients) discontinued due to TEAEs compared to PARAMOUNT (9.2%, 33 patients) [21]. Only 5 patients (10%) discontinued due to CTCAEs of Grade ≥3, which is similar to the overall discontinuation rate in PARAMOUNT, while the remainder (15 [28%]) discontinued due to CTCAEs of Grade 1/2.…”
Section: Discussionmentioning
confidence: 57%
“…Different chemotherapy regimens for advanced NSCLC may cause different distributions of toxicities. Gemcitabine/cisplatin regimen demonstrated more prominent thrombocytopenia, anemia, and renal toxicity, whereas pemetrexed-based regimen was more prone to inducing neutropenia, anemia, and fatigue [29,30]. Toxicities introduced by chemotherapeutic regimens should be considered when analyzing the toxicities of the combined therapies.…”
Section: Study or Subgroupmentioning
confidence: 99%
“…In addition, QoL was evaluated through the standardized EuroQol 5-dimensional scale (EQ-5D). These data demonstrated that patients can tolerate long-term use of continuation maintenance pemetrexed without worsening the QoL [10].…”
mentioning
confidence: 86%